2023
DOI: 10.3390/compounds3030037
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activity of Artemisia argyi Essential Oil and Hydrolate

Remigius Chizzola,
Doris Gansinger

Abstract: Artemisia argyi, Chinese mugwort, is a plant widely used in China for various purposes from traditional medicine to food. The plant is less known in Europe. From plants grown in Austria, essential oils and their respective hydrolates were obtained, and their compositions were studied. Oxidized monoterpenes 1,8-cineole (32–42%), camphor (12–14%), and borneol (10–12%) were the main components present in both the essential oils and hydrolates. The essential oils also contained 6.6–10.5% monoterpene hydrocarbons s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…& Vaniot is a recognized medicinal plant deployed for managing dysmenorrhea, abdominal pain, and inflammation (48). A study identified 69 compounds from A. argyi essential oil (AAEO), with prevalent sesquiterpenes, monoterpenes (1,8-cineole and α-terpineol), and a relatively modest presence of ketones, aldehydes, aromatic, and phenolic compounds (49). Additionally, the study assessed the anti-HBV potential of AAEO, revealing substantial inhibition of HBV DNA replication and HBV antigen secretion (Fig.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…& Vaniot is a recognized medicinal plant deployed for managing dysmenorrhea, abdominal pain, and inflammation (48). A study identified 69 compounds from A. argyi essential oil (AAEO), with prevalent sesquiterpenes, monoterpenes (1,8-cineole and α-terpineol), and a relatively modest presence of ketones, aldehydes, aromatic, and phenolic compounds (49). Additionally, the study assessed the anti-HBV potential of AAEO, revealing substantial inhibition of HBV DNA replication and HBV antigen secretion (Fig.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…Wormwood essential oil has a particularly strong odor, with a warm and sometimes bitter herbal aroma [ 30 ]. Wormwood essential oil has complex chemical components, containing over 75 different compounds [ 31 , 32 ]. The main ingredients include anisaldehyde, anisole, anisone, eucalyptus, camphor, and pinene.…”
Section: Introductionmentioning
confidence: 99%